Worship Attendance and the Disability Process in Community-Dwelling Older Adults - Fitchett, George (Oxford University Press, 2013)
OBJECTIVES. We examined the contribution of religious involvement to age-related declines in health by examining the association of worship attendance with measures of different stages in the disability continuum. METHOD. Participants included 5,863 Black and White older adults from the Chicago Health and Aging Project. Worship attendance was coded in 3 levels: very frequent (several times a week or more), frequent (several times a month), and infrequent (several times a year or less). Measures of disability included self-reported instrumental activities of daily living (IADL) and activities of daily living (ADL) disability as well as observed physical function. RESULTS. In multiple regression models adjusted for demographic factors, compared with those with infrequent worship attendance, those with frequent or very frequent attendance had lower levels of IADL and ADL disability and higher levels of physical performance at baseline. These associations remained significant in models that adjusted for health and cognitive status. There was no association between frequency of worship attendance and change in disability or physical function over time. DISCUSSION. These results suggest that more frequent worship attendance does not contribute to slowing the progress of disability in late life. Future research is needed to better understand the development of the differences in disability associated with worship attendance observed at baseline.